P101 Effects Of Using A Mask Vs. Mouthpiece On The Multiple Breath Inert Gas Washout Technique. (10th November 2014) - Lum, S; Stocks, J; Kozlowska, W; Aurora, P
Abstract : Assessment of ventilation inhomogeneity using the multiple breath washout (MBW) technique has been shown to be more sensitive than spirometry in detecting early cystic fibrosis lung disease throughout childhood. The current "gold standard" interface for school age children and adults is a mouthpiece. Although masks are better tolerated by infants and younger children, their use increases equipment deadspace-which could influence measured values and hence interpretation of results. The aim of this study was to examine the effect of using a mask vs mouthpiece on values of functional residual capacity (FRC) and the lung clearance index (LCI) derived from MBW. Method: Comparisons were performed in healthy adults. The study design incorporated repeated measures as well as interface comparison. The mask was selected to mimic measurement conditions in infants, the deadspace of 85 mL being approximately 1–2 ml/kg in adults. Mouthpiece (MP) deadspace was ~5 ml. Subjects were randomly allocated to group A (Mask-Mouthpiece-Mouthpiece) or group B (Mouthpiece-Mouthpiece-Mask) protocols. Each subject performed a total of 9 MBW runs, in 3 sets, each consisting of 3 runs, with a 5-minute break between each set. MBW was performed using a mass spectrometer as described previously (Aurora 2005 AJRCCM). Paired t-tests with 95% limits of agreement were used to establish repeatability (MP1 vs. MP2) and any differences between Mask vs. Mouthpiece. This study was approved by the local research ethics committee and written consent obtained from subjects. Results: Technically satisfactory comparative data were obtained on 15 occasions in 14 adults (36% males; age: 22–56 years). Respiratory rate and tidal volume were similar using either approach. Repeatability: Both FRC and LCI were repeatable using the mouthpiece [(Mean (95% CI) diff: FRC: 0.012L (-0.05;0.07); LCI: -0.1(-0.3; 0.1)]; Figure 1A and B . Mask vs. Mouthpiece: FRC and LCI were both significantly higher when assessments were made using a mask compared with a mouthpiece: FRC: 0.101L (0; 0.202); LCI: 0.4 (0.2;0.7); Figure 1C and D . Conclusion: The increase in LCI when using a facemask exceeded normal within test variability in adults and could influence interpretation of results especially if different patient interfaces are used when collecting data in younger children.